2018
DOI: 10.3738/1982.2278.3229
|View full text |Cite
|
Sign up to set email alerts
|

Technical Analysis of a Family Dairy Property in Caldas/Mg

Abstract: A pecuária leiteira é fundamental para geração de riqueza e renda em propriedades familiares.Conhecer indicadores de eficiência garante melhoria dos parâmetros de qualidade, produção e rentabilidade da atividade, fundamental para o desenvolvimento da cadeia produtiva do leite. Esse estudo teve por objetivo analisar o desempenho de uma propriedade leiteira familiar por meio dos indicadores zootécnicos e verificar se esses indicadores podem contribuir com o desenvolvimento da atividade em questão. Foi realizada … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…In this study, the decrease in land occupation combined with the increase in the number of LC resulted in 1.66 lactation cow per hectare (LC.ha 1 ), a value higher than 0.70 LC.ha -1 reported by Pereira et al (2016), and higher than 1.18 LC.ha -1 found by Bassotto et al (2018). These authors confirmed that the results obtained in that study were satisfactory for the number of LC per area.…”
Section: Zootechnical Performance Indicatorssupporting
confidence: 88%
See 2 more Smart Citations
“…In this study, the decrease in land occupation combined with the increase in the number of LC resulted in 1.66 lactation cow per hectare (LC.ha 1 ), a value higher than 0.70 LC.ha -1 reported by Pereira et al (2016), and higher than 1.18 LC.ha -1 found by Bassotto et al (2018). These authors confirmed that the results obtained in that study were satisfactory for the number of LC per area.…”
Section: Zootechnical Performance Indicatorssupporting
confidence: 88%
“…The search for a production scale, however, is a preponderant factor in keeping a viable milk production system as, in addition to the volume produced is directly related to the income earned in the activity, it is also the item over which, proportionally, and the farmer has the greatest capacity for influence when compared to the price of the milk. When analyzed economic forecasts on dairy farms in FF as strategic tools for evaluating livestock development, Bassotto et al (2018) found that the milk yield is responsible for maintaining profitability, providing the long-term continuity of productive activities. Table 2 shows the evolution of the main zootechnical indicators in the two productive cycles.…”
Section: Importance Of Production Scalementioning
confidence: 99%
See 1 more Smart Citation
“…Among the farms, the average area intended for dairy activity was 32 ha (Table 3). The mean productivity reached 873 (L/ha/year), similar to the finding by Silva et al (2011) in Pernambuco State (846.42 L/ ha/year) but much lower than those of Moraes et al (2016) in Rio de Janeiro State (13,085.59 L/ha/year) and of Bassotto et al (2018) in the south end of Bahia State (2,146.2 L/cow/year). Lopes et al (2010) observed that smaller farms (ha) achieved higher yields (5,896.20 L/ha/year), while larger ones had worse results (830.66 L/ha/year).…”
Section: Resultssupporting
confidence: 67%
“…As for production per cow (liters/cow/day), the average was 4.0 L, like the average found by Assis (2014) (4.2 liters/ cow/day) in the region of Tarauacá, Acre State. However, lower than the values obtained in other regions of Brazil, namely in Minas Gerais State (13.11 L/cow/day) by Bassotto et al (2018), in Rio de Janeiro State (12.15 L/cow/day) by Moraes et al (2016), and in the central region of Paraná State (6.04 L/ cow/day) by Battaglini et al (2013). Notably, all the studies cited were under pasture production systems.…”
Section: Resultsmentioning
confidence: 71%